Revealing the Integrity of Investigators in Handling Cases of Crimesby Witnesses Perpetrated (Case Study of Alleged Criminal Acts of Vandalism in Central Buton Regency) - Muh Sutri Mansyah; Achmad Busro; Yunanto Yunanto (Association of Certified Fraud Examiners Indonesia Chapter, 2022)
This study aims to examine and analyze the integrity of investigators in handling criminal cases committed by witnesses (Case Study of Alleged Criminal Acts of Vandalism in Central Buton Regency), through a juridical-empirical research approach and analysis of qualitative methods. The results show. To reveal the integrity of investigators, two indicators are used, namely honesty and objectivism. So the results of the study showed that there was dishonesty by the investigators, namely asking for the summons of witnesses at night, the investigator denied the question and said it was not true while regarding objectivism, the investigator allegedly sided with the reporter based on the alleged threat to the witness to admit that he did it. Suggestions in realizing investigators with integrity can be formed through two aspects, namely internal aspects, and external aspects, internal aspects of the police institution must be seriously fostered through quality education of cultural maturity, spiritual maturity, psychological maturity, cultural maturity, conscience maturity, and moral maturity that originates from, external aspects, namely synergies between institutions and integration into a supervisory system.